KITAB-KITAB HADIST SESUDAH ABAD KE 3 H - Abdul Wahab Syakhrani (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
The writing of hadith after the 3rd century H is to rearrange the previous hadith books thematically, both in terms of matan and sanad to make it easier for Muslims to study them, for example Al-Mawdhu'at which is collecting hadiths that are mawdhu '(false) only to in a book, Al-Ahkam, namely collecting hadiths about the law, such as fiqh, and others.